ASSESSING PRINCIPALS’ LEADERSHIP AND INFORMATION TECHNOLOGY SKILLS ON EFFECTIVE ADMINISTRATION IN PUBLIC SECONDARY SCHOOLS IN DELTA STATE - Akpoveta, Ogheneobukome Flora; Prof. E.J Egwunyenga (European Journal of Humanities and Educational Advancements, 2023)
The study examined principals’ leadership and information technology skills for effective administration in public secondary schools in Delta State. In carrying out the study, two research questions were answered and two hypotheses were tested. The study covered all public secondary school principals and teachers in Delta State. The sample of the study is 219 principals and 743 teachers in Delta State public secondary schools. The sampling procedure used is the stratified random sampling technique. A questionnaire was used to collect data from the respondents, and the data were analyzed using coefficients of determination to provide answers to the research questions, while product moment correlation statistics were used to test the hypotheses at the 0.05 level of significance. The findings from the study showed that there is a positive relationship between principals’ leadership skills and effective administration. There is a positive relationship between principals’ information technology skills and effective administration. It was concluded that principals’ leadership skills and principals’ information technology skills positively relate to effective administration. It was recommended, among others, that the principal should acquire the necessary leadership and information technology skills relevant to the school system to enhance effective administrative performance for the growth and development of the institution.